2010
DOI: 10.1111/j.1439-0426.2009.01360.x
|View full text |Cite
|
Sign up to set email alerts
|

Developmental biology of medaka fish (Oryzias latipes) exposed to alkalinity stress

Abstract: Alkalinity stress is common in cultured aquatic animals and considered to be one of the major stress factors for fishes when they are transferred to saline-alkali waters. To evaluate potential effects of alkalinity on the developmental biology of Oryzias latipes, fertilized eggs, larvae and breeding fish were exposed to different carbonate alkalinity concentrations of 1.5-64.5 meq l )1 , for 9, 120, and 60 days, respectively. The mortality of embryos significantly increased when exposed to the high concentrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(20 citation statements)
references
References 27 publications
1
19
0
Order By: Relevance
“…The relative increase in peak post-prandial MO 2 for C. auratus gibelio exposed to high pH reached a maximum of 2.2 times higher than SMR, along with extremely narrow AS, which may result in difficulty getting food and a low ingestion rate. This is consistent with our findings about the growth performance of fish in alkaline water [31]. These findings give us some hint that extra oxygen should be provided when farming the fish in high pH water, especially during the feeding and ingestion period.…”
Section: Effects Of High Ph On Aerobic Metabolismsupporting
confidence: 92%
“…The relative increase in peak post-prandial MO 2 for C. auratus gibelio exposed to high pH reached a maximum of 2.2 times higher than SMR, along with extremely narrow AS, which may result in difficulty getting food and a low ingestion rate. This is consistent with our findings about the growth performance of fish in alkaline water [31]. These findings give us some hint that extra oxygen should be provided when farming the fish in high pH water, especially during the feeding and ingestion period.…”
Section: Effects Of High Ph On Aerobic Metabolismsupporting
confidence: 92%
“…Our present and former studies (Yao et al 2010(Yao et al , 2012 have revealed that medaka is an ideal model organism for studying the effects of saline-alkaline stress in fish and have led to establishment of developmental biology and gene expression protocols for continuing this line of research. Additionally, medaka is aboriginal in some saline-alkaline lakes in China (Zhao 2010) presenting an opportunity for additional comparative studies utilizing medaka and other native species living in these special water bodies, which should aid in revealing the underlying saline-alkaline adaptation mechanisms.…”
Section: Fish Physiol Biochemmentioning
confidence: 98%
“…Six carbonate alkalinity concentrations were tested as shown in Table 1. The selection of alkalinity concentrations was based on a former study by Yao et al (2010). In order to maximize our opportunity for elucidating the key components involved in mechanistic responses for regulating alkalinity stress, the maximum alkaline concentration (30.4 mM) that medaka could survival for a long period time was set as the acute exposure concentration and highest chronic exposure concentration.…”
Section: Test Fishmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, alkalinity causes several abnormal behavioral, physiological, and biochemical reactions and even quick death in freshwater teleosts exposed to alkaline water (Yao et al, 2010). Freshwater fishes can endure alkalinity up to a certain extent (pH close to 8) depending on the species or individuals (Lei et al, 1985).…”
Section: Introductionmentioning
confidence: 99%